The Place Of Public Opinion In The Socio-Political Life Of Society - Ergasheva Maxsuda Pulatovna; Muxammedov Mirjalol (Zien Journals, 2022)
This article analyzes the content of the concept of public opinion, the interpretation of public opinion and its impact on socio-political processes.
Keywords: public opinion; public; social control; political life